Effect of aquifer storage and recovery (ASR) on recovered stormwater quality variability. (15th June 2017) - Page, D.W.; Peeters, L.; Vanderzalm, J.; Barry, K.; Gonzalez, D.
Abstract: Aquifer Storage and Recovery (ASR) is increasingly being considered as a means of reusing urban stormwater to supplement available urban water resources. Storage of stormwater in an aquifer has been shown to affect water quality but it has also been claimed that storage will also decrease the stormwater quality variability making for improved predictability and management. This study is the first to document the changes in stormwater quality variability as a result of subsurface storage at four full scale ASR sites using advanced statistical techniques. New methods to examine water quality are required as data is often highly left censored and so traditional measures of variability such as the coefficient of variation are inappropriate. It was observed that for some water quality parameters (most notably E. coli ) there was a marked improvement of water quality and a significant decrease in variability at all sites. This means that aquifer storage prior to engineered treatment systems may be advantageous in terms of system design to avoid over engineering. For other parameters such as metal(loids)s and nutrients the trend was less clear due to the numerous processes occurring during storage leading to an increase in variability, especially for geogenic metals and metalloids such as iron and arsenic. Depending upon the specific water quality parameters and end use, use of ASR may not have a dampening effect on stormwater quality variability. Highlights: Managed aquifer recharge affects water quality variability. E. coli variability is significantly reduced. For other water quality parameters the trend is less clear. Opportunity to integrate aquifer and engineered water treatment processes.